2020
DOI: 10.1177/2158244020923354
|View full text |Cite
|
Sign up to set email alerts
|

Online Rebellion: Self-Organized Criticality of Contemporary Protest Movements

Abstract: The theory of self-organized criticality (SOC) is applicable for explaining powerful surges of protest activity on social media. The objects of study were two protest clusters. The first was a set of Facebook groups that promoted the impeachment of the Brazilian president Dilma Rousseff. The second was a set of groups on the social network Vkontakte that provided support for anti-government rallies in Armenia, referred to as Electric Yerevan. Numerous groups in the examined clusters were functioning in SOC mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
(26 reference statements)
1
8
0
Order By: Relevance
“…Let us take social media as an example. Recent studies have shown that most social networks are capable to self-organize into the critical state (see the papers [7,[46][47][48][49][50][51]). The mechanisms (local rules) for online social networks (for example, Twitter) for transition into the SOC state are similar to the standard rules of the sandpile cellular automaton on the BA graph.…”
Section: Discussionmentioning
confidence: 99%
“…Let us take social media as an example. Recent studies have shown that most social networks are capable to self-organize into the critical state (see the papers [7,[46][47][48][49][50][51]). The mechanisms (local rules) for online social networks (for example, Twitter) for transition into the SOC state are similar to the standard rules of the sandpile cellular automaton on the BA graph.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there has been strong evidence of the existence of the SOC state on the social networks that is presented in the number of fundamental studies (e.g., see the papers [20][21][22][23][24][25]). e following papers are the most relevant to our research.…”
Section: Introductionmentioning
confidence: 99%
“…Social systems with cooperative dynamics, studied using the dynamical data from online social sites [38,51,[83][84][85], appear to possess the mechanisms of SOC that enable the genesis of collective values from the individual features (knowledge, emotions, and behaviours) of the communicating participants. The same active principle seems to underscore the emergence of languages [86,87], as well as the social protests [88], wars [89], and historical processes [90]. In contrast to the above mentioned physical systems, the interactions underlying social self-organisation have different attributes that are elusive to similar formal theories.…”
Section: Self-organised Critical Systems and Their Network At Different Scalesmentioning
confidence: 98%